Pengaruh Unsur SPIP Terhadap Penatausahaan Aset Tetap (Studi Kasus Pada Pemerintah Kabupaten Bandung Barat) - Wihelmus Freksi Kurniadi; Khozin Arief; Yanti Rufaedah (Indonesian Accounting Research Journal, 2021)
This research aims to determine the influence of the Government's Internal Control System both simultaneously and partially through each element on the Administration of Fixed Assets. The type of research that researchers use is quantitative research. The population of this study is a Regional Device Task Force (SKPD) in West Bandung Regency with a sample of 28 SKPD consisting of the Regional Secretariat, Regional Inspectorate, 20 Agencies and 4 Agencies located in the environment of the West Bandung Regency Government office. From the results of this study, simultaneously elements of the government's internal control system (SPIP) had a positive and significant effect on the administration of fixed assets and partially controlled and monitoring activities of internal control had a positive and significant effect.